Y diversa de mí misma entre vuestras plumas ando : homenaje internacional a Sor Juana Inés de la Cruz - Poot Herrera, Sara; Urrutia, Elena; Juana Inés de la Cruz, Sister, 1651-1695 (El Colegio de México, 1993)
"Superb collection of articles by scholars who participated in the Sor Juana symposium held in Mexico in 1993. Authors look at the nun's diverse works, many previously overlooked, as well as different themes treated by Sor Juana. Highly recommended"--Handbook of Latin American Studies, v. 58.